Gender - Does it affect BT (Bleeding Time) or CT (Clotting Time): A cross sectional study in medical students - Monika Gavali; Yogesh Gavali; Samir Singru; Krishnakant Patil (Al Ameen Medical College, 2016)
Background: Bleeding time (BT) and Clotting time (CT) assess the integrity of haemostatic mechanisms. Haemostasis is the arrest of bleeding. Bleeding time depends on the effectiveness of vasoconstriction as well as platelet plug formation, while Clotting time depends upon the effectiveness of clotting mechanism. Earlier studies done on this showed the conflicting results and conclusion. Objectives: The objective of this study was to identify whether there is any gender difference as between Bleeding time and Clotting time. Method: This was a cross sectional study including 433, undergraduate medical students of age group 17 to 20 years. Bleeding time (by Duke's filter paper method) and Clotting time (by Wright's capillary tube method) was determined after obtaining an informed consent from the students. Result and conclusion: Our study revealed the value of CT was little higher in males but this difference was not statistically significant. Also BT was higher in females as compare to males but again not statically significant.